1981
DOI: 10.2134/jeq1981.00472425001000010016x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Contents of Streams Draining an Agricultural and a Forested Watershed in Central Italy

Abstract: Water samples from an agricultural and a forested watershed (33,180, and 4,090 ha, respectively) were analyzed during the 1979 water year to determine the concentration of NO3‐N, NH4‐N, NO2‐N, and organic‐N. Monthly fluctuations in the concentration of NO3‐N from the agricultural watershed may represent an interaction of organic matter mineralization and N fertilization at the time of seeding. From both watersheds NO3‐N and NH4‐N concentrations do not exceed the upper limits recommended for drinking water.From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…As seen in previous studies, water quality was influenced by the hydrological characteristics of the watershed and by the chemical inputs of natural or anthropogenic Figure 5 Alexander stream annual average flow at Elyashiv station origin, in the watershed (Baker and Richards 2000). These observations from the Alexander stream are also in agreement with data reported by Caporali et al (1981) regarding an agricultural watershed in Tuscany, and Behrendt (1993) for the river Rhine. As expected, dilution was correlated with higher water discharges.…”
Section: Water Qualitysupporting
confidence: 88%
“…As seen in previous studies, water quality was influenced by the hydrological characteristics of the watershed and by the chemical inputs of natural or anthropogenic Figure 5 Alexander stream annual average flow at Elyashiv station origin, in the watershed (Baker and Richards 2000). These observations from the Alexander stream are also in agreement with data reported by Caporali et al (1981) regarding an agricultural watershed in Tuscany, and Behrendt (1993) for the river Rhine. As expected, dilution was correlated with higher water discharges.…”
Section: Water Qualitysupporting
confidence: 88%
“…1], 1991 Habitat Southwood 1977, Barton et al 1985, Statzner and Higler 1985, Statzner et al 1988, Poff and Ward 1989Disturbance Dance and Hynes 1980, Weatherley et al 1989 Factors structuring aquatic ecosystems Minshall et al 1983, Triska 1984, Naiman et al 1988, Townsend 1989 Response to localized phenomena Urban land use: water quality Wolman 1967 (as cited in Gregory 2004), Dillon and Kirchner 1975, Turner et al 1975, Burton et al 1977a, b, Faust and Goff 1977, Karr and Schlosser 1978, Hill 1980Agricultural land use: water quality Omernik 1976, Asmussen et al 1979, Caporali et al 1981, Omernik and Abernathy 1981, Osborne and Wiley 1988, Sharpley et al 1988 Forest harvest impacts on habitat, biota, processes Neary 1976, Gurtz et al 1980, Newbold et al 1980, Webster and Waide 1982, Golladay and Webster 1987, Beschta and Taylor 1988, Bilby 1988, Gregory et al 1991 Large-scale phenomena Minshall et al 1983, Kansanen et al 1984, Bott et al 1985, Frissell et al 1986, Hughes and Larsen 1986, Naiman et al 1987, Minshall 1988, Kr...…”
Section: Phenomenon Referencementioning
confidence: 99%
“…Elsewhere, studies of both large (Asmussen et al 1975;Caporeli et al 1981) and small watersheds (Munn et al 1973;Romkens et al 1973;Schuman et al 1973;Klausner et al 1974;and Hubbard and Sheridan 1983) have been performed to answer questions regarding the net effect of agricultural practices on water quality with time or relative to weather, fertility, or cropping practices. Recent work in the northeastern United States has shown that even on areas not impacted by cattle excreta, a substantial amount of NO 3 -N from inorganic fertilizers can leach below the root zone (Stout et al 1997(Stout et al , 1998(Stout et al , 2000 and contribute to groundwater NO 3 -N concentrations that exceed the 10 mg l -1 drinking water standard (US EPA 1987).…”
Section: Introductionmentioning
confidence: 99%